Health professionals’ stigmatizing attitudes towards people with mental illness: A cross-sectional study in a referral hospital in Uganda - Abaatyo, Joan; Nyemara, Novatus; Ashaba, Scholastic (Public Library of Science, 2024)
Health professionals in primary care settings show stigmatizing attitudes towards people with mental illness (PMI), leading to undermined quality of care delivered. However, information is sparse on stigmatizing attitudes of health professionals towards PMI in Uganda. This study aimed to discover the levels of stigmatizing attitudes towards PMI and associated factors among health professionals in Uganda. We enrolled 254 health professionals at Mbarara Regional Referral Hospital in a cross-sectional study. Community attitude towards mental illness-2 (CAMI-2) scale was used to assess stigmatizing for attitudes. Linear regression was used to determine factors associated with level of stigmatizing attitudes. The average overall CAMI score for all participants was 91.1±16.6. Nurses/midwives compared to doctors had significantly higher total CAMI score (p<0.001), and higher malevolent (p = 0.01) and non-acceptance attitudes (p = 0.02) than doctors. Doctors had significantly lower authoritarian attitudes than clinical officers, (p = 0.004). Being male (aCoef: -4.86; p = 0.02), increase in compassion satisfaction (aCoef: -0.44; p = 0.02), and increased mental health knowledge (aCoef: -2.90; p = <0.001), increased likelihood of having lower levels of stigmatizing attitudes, while being a non-psychiatric health professional was associated with higher levels of stigmatizing attitudes (aCoef: 12.08; p = 0.01). Health professionals exhibit moderate levels of stigmatizing attitudes towards PMI and stigmatizing attitudes are more among nurses/midwives. Various steps including providing education and training on mental illness, promoting community integration and social inclusion, and advocating for policies, should be taken to reduce stigmatizing attitudes of health professionals towards PMI. Gale OneFile: Science